DDX54 Plays a Cancerous Role Through Activating P65 and AKT Signaling Pathway in Colorectal Cancer - Yu, Yi; Wang, Jing-Long; Meng, Li-Li; Hu, Chun-Ting; Yan, Zhao-Wen; He, Zhi-Ping; Shi, Xiao-Qin; Fu, Guo-Hui; Zu, Li-Dong (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most malignant cancers and its incidence is still steadily increasing. The DDX RNA helicase family members have been found to play a role in various cancers, however the role of DDX54 in colorectal cancer is still unclear and needed to be defined. Here we found DDX54 was overexpressed in CRC tissues by the Label-free Mass Spectrum which was also verified in tissue microarray of colon cancer as well as the CRC cell lines and TCGA database. High DDX54 level was correlated with tumor stage and distant metastasis, which always indicted a poor prognosis to the CRC patients. DDX54 could promote the proliferation and mobility of CRC cells through increasing the phosphorylation level p65 and AKT leading to the tumorigenesis. Here we have preliminarily studied the function of DDX54 in CRC, which would improve our understanding of the underlying biology of CRC and provide the new insight that could be translated into novel therapeutic approaches.